The Basal NPO crh Fluctuation is Sustained Under Compromised Glucocorticoid Signaling in Diurnal Zebrafish - Yeh, Chen-Min (Frontiers in Neuroscience, 2015)
The circadian activity of the hypothalamo-pituitary-adrenal/interrenal (HPA/I) axis is crucial for maintaining vertebrate homeostasis. In mammals, both the principle regulator, corticotropin-releasing hormone (crh) in the hypothalamic paraventricular nucleus (PVN) and the final effector, the glucocorticoids show daily rhythmic patterns. While glucocorticoids are the main negative regulator of PVN crh under stress, whether they modulate the PVN crh rhythm under basal condition is unclear in diurnal animals. Using zebrafish larvae, a recently-established diurnal model organism suited for the HPA/I axis and homeostasis research, we ask if glucocorticoid changes are required to maintain the daily variation of PVN crh. We first characterized the development of the HPI axis overtime and showed that the basal activity of the HPI axis is robust and tightly regulated by circadian cue in 6-day old larvae. We demonstrated a negative correlation between the basal cortisol and neurosecretory preoptic area (NPO) crh variations. To test if cortisol drives NPO crh variation, we analyzed the NPO crh levels in glucorcorticoid antagonist-treated larvae and mutants lacking circadian cortisol variations. We showed that NPO crh basal fluctuation is sustained although the level was decreased without proper cortisol signaling in zebrafish. Our data indicates that glucocorticoids do not modulate the basal NPO crh variations but may be required for maintaining overall NPO crh levels. This further suggests that under basal and stress conditions the HPA/I axis activity is modulated differently by glucocorticoids.